Efektivitas Tumpang Sari Tanaman Jagung pada Tanaman Kelapa Sawit dalam Menekan Pertumbuhan Gulma - Rosdiana Br. Sinaga; Putri Widia Salha; Haritsyah Haritsyah; Ibrena Joelta Sitepu; Astrid Aprilia; Guntoro Guntoro (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Weed growth in mature oil palm plantations (MTP) is a major problem due to competition for light, water, nutrients, and growing space. Intensive chemical weed control has the potential to cause resistance, environmental pollution, and increase production costs. The corn intercropping system in mature oil palm plantations (MTP) provides an ecological weed control alternative. This study aims to synthesize scientific evidence on the effectiveness of corn intercropping in suppressing weed growth in mature oil palm plantations using the Systematic Literature Review (SLR) method. Literature searches were conducted on Google Scholar, DOAJ, Garuda, and university repositories for the 2015–2025 period. Of the 50 scientific papers that met the inclusion criteria, 50 were analyzed in depth. The synthesis results showed that corn intercropping can reduce weed density by 35–70%, suppress weed biomass by up to 60%, reduce the dominance of grass and sedge weeds, and reduce the frequency of chemical weeding from 4 to 1–2 times per season. Weed suppression occurs through mechanisms such as rapid canopy closure, competition for growing space, and changes in soil microclimate. These findings confirm that corn intercropping is effective as an economical and environmentally friendly weed control strategy in TM oil palms.